2017
DOI: 10.4236/jep.2017.81007
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Some Heavy Metals in Water and Sediment at Marsa-Matrouh, Mediterranean Sea, Egypt

Abstract: In an attempt to evaluate the environmental quality of Marsa-Matrouh city which covered the most famous beaches in Egypt, an environmental risk assessment was performed, including a screening level ecological risk assessment. The aim of this work was to determine which metals could possibly pose toxic adverse ecological effects to marine organisms and to determine whether hot spots exist or not. To fulfill the goals of study, surfacial sediment and water samples were collected from ten different locations cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…Copper concentrations in this study was higher than those reported by [36] in both dry (0.36 mg/L) and wet (0.07 mg/L) season collected from Ogbere River, Ibadan. However, the Cu value (9.307 mg/L) reported by [37] in Marsa Matrouh, Mediterranean, Egypt River was close to the value obtained in this study.…”
Section: Levels Of Trace Metals In Water Samples In Mg/lsupporting
confidence: 88%
“…Copper concentrations in this study was higher than those reported by [36] in both dry (0.36 mg/L) and wet (0.07 mg/L) season collected from Ogbere River, Ibadan. However, the Cu value (9.307 mg/L) reported by [37] in Marsa Matrouh, Mediterranean, Egypt River was close to the value obtained in this study.…”
Section: Levels Of Trace Metals In Water Samples In Mg/lsupporting
confidence: 88%
“…The PI L value provides a comparative means for assessing a site's quality, where a value of PI L < 1 indicates no contamination with the studied metals; when PI L = 1, the baseline levels of pollutants are present; whereas a value of PI L > 1 indicates that, on average, the element concentrations are above the permissible levels, and a deterioration of the site quality is registered, as shown in Table 5 [24,25]. The geo-accumulation index (I geo ) of a sample site was calculated according to the relation shown in the Equation (3) [20,21,26,27]:…”
Section: Soil Contamination Factor (Cf)mentioning
confidence: 99%
“…Empero, las variaciones ambientales pueden provocar la liberación de estas sustancias acumulativas y tóxicas adheridas a las partículas del sedimento hacia el agua, donde son más disponibles química y biológicamente (Fuentes, 2010). En específico, cuando estas especies químicas cautivas están presentes en cantidades superiores a una concentración umbral pueden causar efectos tóxicos adversos a los organismos vivos e impactar indirectamente la salud humana, por ello cualquier contaminante que ingrese al medio marino afecta, de forma potencial, la ecología (Khaled et al 2017;Fuentes, 2010).…”
Section: Introductionunclassified